Scavenging of reactive oxygen species by phenolic compound-modified maghemite nanoparticles - Świętek, Małgorzata; Lu, Yi-Chin; Konefał, Rafał; Ferreira, Liliana P; Cruz, M Margarida; Ma, Yunn-Hwa; Horák, Daniel (Beilstein journal of nanotechnology, 2019)
Maghemite (γ-Fe2O3) nanoparticles obtained through co-precipitation and oxidation were coated with heparin (Hep) to yield γ-Fe2O3@Hep, and subsequently with chitosan that was modified with different phenolic compounds, including gallic acid (CS-G), hydroquinone (CS-H), and phloroglucinol (CS-P), to yield γ-Fe2O3@Hep-CS-G, γ-Fe2O3@Hep-CS-H, and γ-Fe2O3@Hep-CS-P particles, respectively. Surface modification of the particles was analyzed by transmission electron microscopy, dynamic light scattering, attenuated total reflection Fourier transform infrared spectroscopy, and thermogravimetric analysis. Magnetic measurements indicated that the polymer coating does not affect the superparamagnetic character of the iron oxide core. However, magnetic saturation decreased with increasing thickness of the polymer coating. The antioxidant properties of the nanoparticles were analyzed using a 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. Cellular uptake and intracellular antioxidant activity of the particles were evaluated by an iron assay and flow cytometry, respectively, using L-929 and LN-229 cells. Compared to the control, the phenolic modification significantly reduced intracellular reactive oxygen species (ROS) levels to 35-56%, which was associated with a 6-8-times higher cellular uptake in L-929 cells and a 21-31-times higher cellular uptake in LN-229 cells. In contrast, γ-Fe2O3@Hep particles induced a 3.8-times and 14.9-times higher cellular uptake without inducing antioxidant activity. In conclusion, the high cellular uptake and the antioxidant properties associated with the phenolic moieties in the modified particles allow for a potential application in biomedical areas.
Keywords: antioxidants; phenolic compound; chitosan; maghemite nanoparticles; oxidative stress